Assessment of patient dose from CT localizer radiographs. Issue 8 (12th July 2013) - Schmidt, Bernhard; Saltybaeva, Natalia; Kolditz, Daniel; Kalender, Willi A.
Abstract : Purpose: : With recently introduced technical innovations for CT systems, the dose of CT scan acquisitions has been substantially reduced; even effective dose values below 1 mSv have been reported. Due to this development, dose of the localizer radiograph may contribute substantially to dose of the whole CT examination. Since there are only limited data in the literature regarding patient dose for the different types of localizer radiographs, patient dose values were estimated in our study by measurements and Monte Carlo simulations and compared to dose values of typical CT examinations. Methods: : First, dose distributions were measured in anthropomorphic phantoms for three different body regions (head, thorax, abdomen‐pelvic) and three positions of the x‐ray tube (AP, PA, and lateral views); measured values were compared to simulated data using Monte Carlo techniques for validation purposes. Second, organ and effective dose values for the various investigated localizer radiograph scenarios were calculated and compared with published dose values for standard CT and low‐dose CT examinations. Results: : For the anthropomorphic phantom, deviations of the dose values between measured and calculated results were in the range of 15%. Organ and effective dose values showed a strong dependence on the tube position. The largest differences were observed for chest localizer radiographs in the female phantom for the dose to the breast (AP: 1.01 mGy vs PA: 0.24 mGy). Overall effective dose values were in the range of 0.04–0.42 mSv per localizer radiograph acquisition. Conclusions: : In view of the technical dose‐reducing innovations in CT, localizer radiographs may substantially contribute to the total dose of the whole CT examination, particularly in the case of dedicated low‐dose scans used, e.g., for young patients or screening purposes. Optimization of dose in localizer radiographs should be pursued further in the same way as it was done in CT.